2018
DOI: 10.21109/kesmas.v12i3.1099
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Insurance on Institutional Delivery in Indonesia

Abstract: Institutional delivery has an impact on the decline in maternal mortality rate. In Indonesia, institutional delivery increases every year, but there are still 30%-37% mothers who deliver at home. Unfortunately, the increase is not in line with maternal mortality reduction, so that Indonesia does not achieve the fifth MDGs goal. To achieve Universal Health Coverage, Indonesia implements National Health Insurance (NHI). NHI integrates four types of health insurance, namely Askes/ASABRI, Jamsostek, Jamkesmas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The prevalence of internet usage, with its high interactivity and accessibility, particularly on sensitive subjects like reproductive health [ 39 ], is believed to play a pivotal role in assisting pregnant women in their decision-making during the early stages of pregnancy [ 40 ]. Similarly, women with health insurance showed reduced odds of dropout from the CoC, findings consistent with other study studies [ 41 , 42 ]. This could be attributed to the role of health insurance in overcoming financial barriers that often impede access to maternal health service [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of internet usage, with its high interactivity and accessibility, particularly on sensitive subjects like reproductive health [ 39 ], is believed to play a pivotal role in assisting pregnant women in their decision-making during the early stages of pregnancy [ 40 ]. Similarly, women with health insurance showed reduced odds of dropout from the CoC, findings consistent with other study studies [ 41 , 42 ]. This could be attributed to the role of health insurance in overcoming financial barriers that often impede access to maternal health service [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among studies included in the review, a majority was from India (n=30, 48 %) . There were 11 studies from Nepal (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , 10 from Bangladesh (53)(54)(55)(56)(57)(58)(59)(60)(61)(62) , six from Indonesia (63)(64)(65)(66)(67)(68) and two from Timor-Leste 69,70 . From Bhutan 71 , Thailand 72 , and Myanmar 73 one from each was identi ed.…”
Section: Resultsmentioning
confidence: 99%
“…They further provide contracting in EmOC specialists in private sector as a measure to reduce maternal mortality 29 . In Nepal, Bangladesh and Indonesia, there are similar programmes to facilitate maternal care including institutional delivery 42,43,52,57,59,63,64,66,67 . For the improvement of access to needy mothers and children, government of India has provided accreditation of private sector health providers in government-led schemes for maternity services.…”
Section: B Healthcare Financingmentioning
confidence: 99%
“…Insurance coverage and travel time were stronger predictors of facility delivery for women who delivered a sick neonate in an LLDF; while insurance coverage also promoted hospital delivery for all women and women whose neonate’s illness began in the DH. Other studies have shown a positive effect of NHI coverage on institutional delivery in Indonesia [ 41 , 42 ]. To our best knowledge, this is the first study to examine the effect of any insurance coverage, including private insurance and government assistance to beneficiaries not covered by NHI, on facility delivery.…”
Section: Discussionmentioning
confidence: 99%